BUSINESS VIABILITY OF COOPERATIVE SUGAR FACTORY IN MAHARASHTRA STATE – A CASE STUDY ON SHREE VIGHNAHAR COOPERATIVE SUGAR FACTORY - P. RADHIKA, PRIYANKA, SEEMA and (The Journal of Research, PJTSAU, 2019)
Sugar is one of the most important commodities produced and consumed around the world. Sugar is produced in over 123 countries worldwide but over 70 per cent of world sugar production is consumed domestically and the remaining is traded in the world. Since only a small proportion of world production is traded freely, sugar prices have been volatile in the world market.